GAMBARAN INSOMNIA PADA LANSIA DI PANTI SOSIAL TRESNA WERDHA (PSTW) KHUSNUL KHOTIMAH PEKANBARU: Description of Insomnia in elderly at Panti Sosial Tresna Werdha (PSTW) Khusnul Khotimah Pekanbaru - AULIA GAWARA (Jurnal Medika Hutama, 2024)
Insomnia became part of sleep disorder which happen mostly in elderly. The aim of this research was to know the description of insomnia in elderly with descriptive design. The research used purposive sampling involucing 37 elderly that were selected based on inclusion and exclusion criteria by Jakarta Biology Psychiatry Study Group-Insomnia Rating Scale (KSPBJ-IRS). The univariat analysis was attached to determine the frequency distribution and it showed that 21 (56,8%) were 60-74 years old and 24 (64,9%) people were male, the difficulty started to sleep component were 15 people (40,5%), suddenly woke up at night component were 16 people (43,2%), woke up early were 17 people (45,9%), sleepy during the day component were 13 people (35,1%), headache during the day component were 18 people (48,6%), feels less satisfied with sleep component were 17 people (45,9%), feels less comfortable/restless when sleeping component were 15 people (40,5%), had nightmares component were 22 people (59,5%), body felt weak, tired, lacked energy after sleeping component were 17 people (45,9%), schedule sleep hours until wake up irregularly were 19 people (27,0%), the sleep for 8 hours a night component were 21 people (56,8%), and the description of insomnia was majority in minor insomnia for 22 people (59,5%). The description of the majority of insomnia were 22 people (59,5%). This research is expected to increase role of nurses especially in providing health promotion about insomnia and importance of sleep needs especially in elderly. Keywords: Elderly, Insomnia, Sleep